2018
DOI: 10.19277/bbr.15.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Physical-sensory evaluation of a cereal bar with quinoa: a preliminary study

Abstract: Nut. Food Sciences │ C. Nut. AlimentaçãoBiomed Biopharm Res. , 2018; (15) 1: , 25-36 Biomedical and Biopharmaceutical Research J o r n a l d e I n v e s t i g a ç ã o B i o m é d i c a e B i o f a r m a c ê u t i c a 25Physical-sensory evaluation of a cereal bar with quinoa: a preliminary study Avaliação físico-sensorial AbstractThe consumption of cereal bars has increased in recentyears because it is a quick and practical way to eat. Cereal bars are products obtained by blending dry ingredients and binder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Other technological applications of quinoa flour involve gelation, water-holding and foaming capacity (Abugoch et al, 2008). This technological versatility of quinoa supports its excellent capacity to substitute wheat flour in the elaboration of cookies (Jan, Panesar, & Singh, 2018) and other bakery products (Garcia et al, 2018), gluten-free pasta (Lorenzo, Sosa, & Califano, 2018), cereal bars (Kaur, Ahluwalia, Sachdev, & Kaur, 2018), and even its use as milk replacer (Jeske, Zannini, Cronin, & Arendt, 2018). However, the high content of sensitive compounds (i.e., unsaturated fatty acids, proteins, antioxidants, vitamins, starch) represents a great challenge for technological processes, limiting the stability of the obtained products.…”
Section: Introductionmentioning
confidence: 89%
“…Other technological applications of quinoa flour involve gelation, water-holding and foaming capacity (Abugoch et al, 2008). This technological versatility of quinoa supports its excellent capacity to substitute wheat flour in the elaboration of cookies (Jan, Panesar, & Singh, 2018) and other bakery products (Garcia et al, 2018), gluten-free pasta (Lorenzo, Sosa, & Califano, 2018), cereal bars (Kaur, Ahluwalia, Sachdev, & Kaur, 2018), and even its use as milk replacer (Jeske, Zannini, Cronin, & Arendt, 2018). However, the high content of sensitive compounds (i.e., unsaturated fatty acids, proteins, antioxidants, vitamins, starch) represents a great challenge for technological processes, limiting the stability of the obtained products.…”
Section: Introductionmentioning
confidence: 89%
“…Diversos ingredientes podem ser adicionados às barras de cereais, desde que não descaracterize o produto, sendo produtos compostos por diversas matérias-primas, constituídos em maior fração de cereais (Garcia et al, 2018), como os utilizados na presente revisão: flocos de arroz, flocos de aveia, e o grão de quinoa. Os demais ingredientes secos utilizados como semente de linhaça dourada, maltodextrina, farinha de batata doce, betaína, colágeno, banana passas e canela em pó, e os ingredientes aglutinantes como mel, xarope de glicose, e goma xantana.…”
Section: Matérias-primas Utilizadas Em Barra De Cereaisunclassified
“…Further, in steaming method of cooking the foods are cooked slowly and are easily digestible with good nutritional profile (Srilakshmi, 2007) [31] . Literature cited indicated that researchers indifferent parts of world conducted studies on development of quinoa salad, porridges, soup and health drinks and has been recently used to develop breakfast cereals; granola bars (Garcia et al, 2018) [9] . Owning to its nutritional benefits, it is used for the production of healthy snacks (Priyanka et al, 2017) [24] .…”
Section: Introductionmentioning
confidence: 99%